Similaridade e composição das samambaias e licófitas em fragmentos de floresta atlântica no nordeste do Brasil - Barros, Samara Cristina Alves de (2013)
Distinct populations of species can be established in an ecosystem because of environmental conditions and/or dispersal ability. Based on this, ferns and lycophyta have been used in ecological studies that evaluate how to make the occupation of these groups in the environment. For that two important theories are employed: the Theory of Niche the Theory and Neutral. Aiming to investigate the wealth distribution of species, from these theories, and inferences about conservation status in fragments of Atlantic Forest in Paraíba, were analyzed for similarities and relationships between geographic distance and environmental conditions on the composition of ferns and lycophyta the fragments. In similarity analysis, two groups were formed. The first, represented by Altitude Wetlands of the Mata of Pau Ferro and Mata of Goimunduba, and the second formed by forests near the coast: PRNP Pacatuba, Mata of Pau-Brazil, and Mata Xem- Xem. It can be inferred that this similarity occurred because of altitudes and temperatures in shared fragments. It was observed that the ferns and lycophyta have distribution and composition in fragments more determined by environmental conditions than by geographical areas, occupying thus the habitats according to the Niche Theory. Based on the flora of ferns and lycophyta occurring, it is observed that the Mata of Pau-Brazil's and Mata Xem xem have low-wealth, which can be attributed to the level of conservation of the fragments, while the PRNP Pacatuba comes in a relative conservation level, which leads consequently to a higher richness.